Enacting power and constructing gender in cervical cancer screening encounters between transmasculine patients and health care providers - Peitzmeier, Sarah M. (Cult Health Sex, 2019)
Transmasculine people are at risk of cervical cancer but have lower rates of cervical cancer screening than cisgender women. Disaffirmation of the patient’s gender and unequal power dynamics between patient and provider during screening contribute to patient unwillingness to be screened. The mechanisms by which the balance of power may be shifted between patient and provider, and by which gender is constructed during the Pap test, are not well understood. A qualitative study using a modified grounded theory approach was undertaken to analyse patient interview and provider interview and focus group data pertaining to power and gender in the context of cervical cancer screening among transmasculine individuals. The study was conducted at an LGBTQ-focussed health centre in Boston, USA. Processes by which power is enacted included constraining or affirming patient choice, mitigating or exacerbating vulnerability, and self-advocacy. Gendering processes included naming patients and their bodies, invoking gender norms, de-gendering/re-gendering Pap tests, and othering or normalising trans bodies. The interplay between these processes promotes or constrains patient agency over body and health, impacting patient care, patient–provider interaction, and service utilisation. Understanding patient and provider roles in power and gender dynamics are critical for the provision of patient-centred care.